A policialização da violência em meio escolar - Windson Jefferson Mendes de Oliveira (2008)
This thesis deals with violence in schools, from the experiences of the Polícia Militar de Minas Gerais (PMMG) from 1988 to 2007, by the policing of schools in Belo Horizonte. Its aims to clarify the mechanisms that cause the current dominant perception about this issue be shaped by a police vision, so that, increasingly, educators and educational administrators lose space in the public debate on the subject. This research is characterized as exploratory, and about the nature, as qualitative. It was used bibliographic and documentary procedures, through out interviews, to build the object of study. There are, moreover, traces of inductive reasoning and techniques of historical method. It is investigated the process of construction of the ideal model of military policeman in Minas Gerais, in a modern society, with analytical references the use of force and the appearance of the police image as the axis of approximation of PMMG with the school. Also, the knowledge and police powers produced by the police force are analyzed in face of its performance at schools. The research shows that the construction of polices "new image" "School's Angels" did not eliminate, at any time, its matrix ambiguity, ie, to be among the transcendent and rational, in order to be one of the strategies for schools approaching. Finally, it was concluded that it is possible to have a police force that acts on law enforcement and peacekeeping, that school policing is a kind of source from which can be extracted the fluids of this police practice and that the wealth that has been the meeting of the school and police has not be sufficiently recognized yet.